COST EFFECTIVENESS OF QUALITY MANAGEMENT SYSTEM IN A REINFORCED CONCRETE FRAME CONSTRUCTION COMPANY - Oladokun, Michael Gbolagade; Fashina, Abimbola Yewande; Mac-Barango, Dumo O. (Journal of Technology Management and Business, 2017)
The main purpose of this research is to determine cost effectiveness of implementing and maintaining quality management system using existing data from information filled in nonconformity report over a period of 4 years (2011 to 2014). The research uses a single case study research design to fulfill the objectives of the study. The data extracted from the annual account of the reinforced concrete frame construction company were analysed. The findings suggest that the company under study has implemented a quality management system within their organisation. The findings show that the cost of quality conformance increases from 2011 to 2014 except for 2013 which is lower than that of 2011 due reduced working months of the quality manager in that year. For the cost of quality non-conformance, the findings show that about 77% of the total value are not recovered by the company in 2012, while this is reduced to about 18% in 2014 due quality management system put in place by the company. It was also shown that the ratio of profit before tax (PBT) to turnover declined by 2.86% in 2012 and by 17.14% by 2013 while it declined by 10% in 2014 when compared to 2011.Â  The study concluded that commitment of the company to quality management system has rubbed off the company of some revenues in the form of profit that would have accrued into the cover of the company. However, the implementation of the quality management system is paying off on its own right. The study recommended that one of the areas that researchers need to give proper attention is to conduct more studies on a number construction companies in order to create an industry norm.